2013
DOI: 10.3389/fpls.2013.00327
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation stress and tolerance in green algae: consequences for ultrastructure, physiological and molecular mechanisms

Abstract: Although most green algae typically occur in aquatic ecosystems, many species also live partly or permanently under aeroterrestrial conditions, where the cells are exposed to the atmosphere and hence regularly experience dehydration. The ability of algal cells to survive in an air-dried state is termed desiccation tolerance. The mechanisms involved in desiccation tolerance of green algae are still poorly understood, and hence the aim of this review is to summarize recent findings on the effects of desiccation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(206 citation statements)
references
References 174 publications
(265 reference statements)
3
192
0
4
Order By: Relevance
“…A higher number of plastoglobules was also observed in plants exposed to several types of stress, e.g. heavy metals for macrophytes (Basile et al 2012a, b) and the lichen X. parietina (Paoli et al 2013(Paoli et al , 2014a, drought for mosses and green algae (Fernández-Marín et al 2013;Holzinger and Karsten 2013) and light stress for algae (Holzinger et al 2004;Holzinger and Lütz 2006). Therefore, the increase in plastoglobules cannot be regarded as a plant-or stress-type specific response.…”
Section: Ultrastructural Effectsmentioning
confidence: 82%
“…A higher number of plastoglobules was also observed in plants exposed to several types of stress, e.g. heavy metals for macrophytes (Basile et al 2012a, b) and the lichen X. parietina (Paoli et al 2013(Paoli et al , 2014a, drought for mosses and green algae (Fernández-Marín et al 2013;Holzinger and Karsten 2013) and light stress for algae (Holzinger et al 2004;Holzinger and Lütz 2006). Therefore, the increase in plastoglobules cannot be regarded as a plant-or stress-type specific response.…”
Section: Ultrastructural Effectsmentioning
confidence: 82%
“…An extensive classical literature about tolerance and recovery to desiccation already exists (Stevenson et al 1996;Holzinger and Karsten 2013). There is good knowledge of the resistant structures such as zygotes, akinetes, or cysts that algae produce under unfavourable conditions and that allow cells to be viable upon rewetting even after months, years and decades of desiccation (Davis 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Holzinger and Karsten (2013) found that some of these physiological strategies in green algae already adapted to desiccation favour a quick recovery when rewet, whereas aquatic species were more sensitive to drying. It has been shown that cyanobacterial mats in Antarctic environments recover photosynthetic activity, similar to rates before desiccation, in few minutes (Vicent and Howard-Williams 1986;Hawes et al 1992;McKnight et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resistance to severe dehydration stress, known as desiccation tolerance, has been well documented for cyanobacteria and lichens. Several studies also highlight phylogenetic lineages of green-algae that are able to develop efficient survival strategies against desiccation [5,43].…”
Section: Aquatic Atmosphere Microbiologymentioning
confidence: 99%